Impact of Crisis Management Strategies on Destination Market Recovery - Shah, Firdous Ahmad; Hussain, Sarah (Prabandhan: Indian Journal of Management, 2024)
Purpose : The paperâ€™s primary objective was to analyze the impact of crisis management strategies on destination market recovery in the Kashmir region. In doing so, the study answered the question regarding the effectiveness of crisis management strategies in recovering a destination that has experienced numerous crises. Methodology : A descriptive research design was used in the study. To document the answers from various tourist stakeholders, a standardized questionnaire was created. A total of 318 comprehensive answers were documented. Regression analysis was used to evaluate the hypothesis after the data were processed using SPSS 25.0. Findings : Strategies were found in six different factors: knowledge exchange, training, security, promotion, communication, and rehabilitation. Prior to analyzing each item separately through regression analysis, all of the crisis management strategy items were first examined as a single component. Regression research revealed that crisis management enhances destination market recovery significantly. Implications : Policymakers and destination market organizations will be able to better grasp the value and efficacy of crisis management techniques, thanks to the studyâ€™s findings. Additionally, it would support scholars and researchers in their ongoing studies on the resilience and recovery of destination markets. Originality : A substantial body of literature has been written about tourism crisis management, but remarkably few studies have focused on the crisis management process itself, which would highlight the recovery of destination markets â€œduring the crisisâ€ and the efficacy of crisis management tactics. By examining the effect of crisis management techniques on destination market recovery, the current study filled this research void.